2002
DOI: 10.1038/sj.onc.1205727
|View full text |Cite
|
Sign up to set email alerts
|

Heterozygosity for p53 promotes microsatellite instability and tumorigenesis on a Msh2 deficient background

Abstract: In colorectal tumorigenesis, loss of function of the mismatch repair genes is closely associated with genomic instability at the nucleotide level whereas p53 deficiency has been linked with gross chromosomal instability. We have addressed the contribution of these two forms of genetic instability to tumorigenesis using mice mutant for Msh2 and p53. As previously reported, deficiency of both genes leads to rapid lymphomagenesis Here we show that heterozygosity for p53 also markedly reduces survival on an Msh2 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 34 publications
5
29
1
1
Order By: Relevance
“…Given previous reports that one mutation of Mbd4 can accelerate MSI, tumours were assessed for instability at four microsatellite loci Toft et al, 2002). Four microsatellite loci were chosen for analysis: D1Mit4, D7Mit17, D10Mit2 and D14Mit15.…”
Section: Loss Of Mbd4 Does Not Increase Tumour Onset Spectrum or Msimentioning
confidence: 99%
“…Given previous reports that one mutation of Mbd4 can accelerate MSI, tumours were assessed for instability at four microsatellite loci Toft et al, 2002). Four microsatellite loci were chosen for analysis: D1Mit4, D7Mit17, D10Mit2 and D14Mit15.…”
Section: Loss Of Mbd4 Does Not Increase Tumour Onset Spectrum or Msimentioning
confidence: 99%
“…Mbd2 and p53 mutant animals were derived from a colony segregating for Ola/129 and C57BL6J genomes, which had been backcrossed three generations onto the C57BL6J background and so were predominantly (87.5%) C57/BL6J. Mice were genotyped by PCR as previously described (Toft et al, 2002;Sansom et al, 2003). Cohorts of at least 18 mice were monitored and harvested when they exhibited symptoms of disease.…”
Section: Loss Of Mbd2 Does Not Accelerate P53-mediated Lymphomagenesismentioning
confidence: 99%
“…The orientation of the RGC and the mutated RGC motif was the same within all three SV40 genomes. Third, to challenge a potential recombination regulatory role of p53 directed toward repetitive DNA sequences in general (Ahrendt et al, 2000;Gebow et al, 2000;Danaee et al, 2002;Toft et al, 2002), we inserted a triplet repeat consisting of 98 CTG copies that causes enhancement of intermolecular recombination in an Escherichia coli plasmid system (Bowater et al, 1996;Pluciennik et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, microsatellite instabilities at tetranucleotide repeats were found to be associated with p53 mutations in skin, bladder, and lung cancer (Ahrendt et al, 2000;Danaee et al, 2002). Finally, on the basis of examinations in thymic lymphomas from MSH2/p53 intercrossed mice, it was proposed that p53 modulates microsatellite instabilities and becomes essential to this process after loss of MSH2 (Toft et al, 2002). In this study, a threefold recombination enhancement was conferred by the (CTG) 98 microsatellite repeat in the parental line without wtp53, which is consistent with previous studies that suggested that homologous recombination is the mechanism underlying instabilities at this triplet repeat within the myotonic dystrophy locus (Richard and Paques, 2000).…”
Section: Discussionmentioning
confidence: 99%